2020
DOI: 10.1186/s40164-020-00172-4
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 induced thrombocytopenia as an important biomarker significantly correlated with abnormal coagulation function, increased intravascular blood clot risk and mortality in COVID-19 patients

Abstract: Background: Coronavirus disease 2019 (COVID-19) is a novel infectious viral disease, which lacks well-established diagnostic laboratory parameters that could be used to evaluate disease severity, thromboembolism or cardiovascular events and to predict clinical prognosis. Coagulation cascade and platelet functions have not been well studied in the COVID-19 patients. Methods: A total of 178 patients enrolled in Wuhan Huoshenshan Hospital were included for the study. Blood platelets and coagulation functions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
3
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 20 publications
8
83
3
5
Order By: Relevance
“…Han et al [5] also reported that there was no significant difference in PT between patients with different levels of severity of COVID-19 and healthy controls. However, more studies reported that severe patients had significantly prolonged PT compared with non-severe patients [16][17][18]. In addition, two studies on COVID-19 indicated that non-survivors had higher PT levels than survivors [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [5] also reported that there was no significant difference in PT between patients with different levels of severity of COVID-19 and healthy controls. However, more studies reported that severe patients had significantly prolonged PT compared with non-severe patients [16][17][18]. In addition, two studies on COVID-19 indicated that non-survivors had higher PT levels than survivors [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 may predispose to not only venous but also arterial thromboembolic disease because of the effects of comprehensive factors including excessive inflammation, platelet activation, endothelial dysfunction, and stasis [ 7 , 14 ]. Platelet is the initiating factor in arterial thrombosis; however, thrombocytopenia is reportedly more common in patients with severe COVID-19 [ 2 , 3 , 13 , 15 , 16 ]. Thrombocytopenia is attributed to abnormal hemostasis and DIC, and is associated with severe disease manifestation and increased mortality in patients with COVID-19 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins like A2M, SERPINA4, SERPINA3, SERPING1, and FGG that are involved in regulated exocytosis of platelets were upregulated in the severe cohort suggesting an increased consumption of platelets. This could be a possible reason for the lower platelet count (clinically called thrombocytopenia) commonly reported in many severe cases of COVID-19 50 , which is also associated with coagulation abnormalities, disease severity, and mortality [51][52][53] . There is enough evidence to suggest that aside from their role in hemostasis, platelets have potent immune and in ammatory effector functions.…”
Section: Discussionmentioning
confidence: 99%